A narrative inquiry of Malaysian parents’ and caregivers’ experiences in detecting autism and providing interventions - Sani, Badariah; Wan Chik, Muhmad Noor; Raslee, Nor Nadia; Badzis, Mastura (TEXTROAD Publishing Corporation, 2017)
There is a lack of knowledge among Malaysian parents in detecting signs of autism in their children. This situation could lead to late detection and intervention. Children’s condition would be harder to improve and this would affect the parents’ and caregivers’ well-being. This study explored parents and caregivers’ experiences in recognizing signs of autism and providing intervention for their autistic children at home. The study used a qualitative research approach with a narrative inquiry method. A total of eleven respondents were interviewed. In-depth interviews and four non-participant observations were carried out. The study found ten signs of autism that parents and caregivers had noticed in their children’s behaviour. Children’s lack of speech or delay in speaking was common and the most noticeable sign for all eleven respondents. The respondents admitted having no knowledge and awareness about autism or signs of autism at the beginning. The periods before and after the detection of autism were difficult periods and many respondents had expressed feelings of sadness, worried as well as frustration. The severity of autism played an important role in alerting parents or caregivers to speed up the process of investigation. Respondents had used many types of interventions for their children and these included behavioural, developmental, family based, therapy based, alternative interventions and medications. Islamic practices were also used by Muslim respondents. The findings gave added knowledge and information on Malaysian parental concerns about signs of autism and provide suggested interventions for parents in caring for their autistic child.